The Effect of Economic Regulations on Foot-and-Mouth Disease on the Cattle Industry in Muria Raya: An Analysis of Commercial and Socio-Economic Losses Families of cattle farmers who have suffered - Supriyadi, Supriyadi; Latif, Moh Abdul (Universitas Islam Negeri Sunan Kudus, 2025)
The Foot and Mouth Disease (FMD) outbreak in Central Java has raised serious concerns regarding high transmission rates, economic losses, and weak biosecurity at the farmer level. This situation calls for more effective regulations and management strategies from the government. This study aims to analyze the economic impact of the FMD outbreak, identify the factors causing the spread of the disease, and evaluate the socio-economic implications for farmers and the community. The study employs a qualitative approach, utilizing data collection methods such as observation, in-depth interviews with farmers in the Pati, Rembang, and Kudus districts, and literature review. Data were analyzed using descriptive analysis techniques, including categorization and data reduction. The results of the study indicate that the FMD outbreak in Muria Raya was caused by the entry of infected livestock through cattle traders from East Java and Aceh, exacerbated by the government's delayed response and limited access to vaccination. The Central Java Provincial Government has issued various regulations and formed a Rapid Response Unit (URC), but its implementation faces obstacles in the form of uneven vaccine distribution. The economic impacts include direct losses such as livestock deaths and reduced productivity, as well as indirect losses such as supply chain disruptions and loss of market access due to zoning policies and the closure of animal markets for over a month. The socio-economic implications of the PMK outbreak are significant for livestock farmers' families, including reduced income, increased costs for traditional medicine, forced borrowing, and education expenses for children. This study concludes that handling FMD outbreaks requires an integrated approach through regulatory strengthening, responsive government economic support, and a risk factor-based prevention system. Successful control depends heavily on synergy between the government, farmers, and stakeholders to minimize socio-economic impacts.